2018
DOI: 10.1016/j.erss.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Kids and Kilowatts: Socialisation, energy efficiency, and electricity consumption in New Zealand

Abstract: Socialisation into electricity consumption usually occurs during childhood, but little is known about the socialisation processes involved. Here, we use interviews and focus groups to investigate how nine to ten-year-old children from New Zealand learn about, and consume, electricity in their homes. The children used a wide range of electrical appliances and engaged in different energy saving behaviours, often without being conscious of their implications. Control over appliances and learning through modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
(127 reference statements)
2
15
0
1
Order By: Relevance
“…Namely, young children as a result of school education on energy and environmental protection principles could encourage parents and relatives towards a lower carbon lifestyle and more sustainable household patterns. This finding was also suggested by [17].…”
Section: Discussionsupporting
confidence: 79%
“…Namely, young children as a result of school education on energy and environmental protection principles could encourage parents and relatives towards a lower carbon lifestyle and more sustainable household patterns. This finding was also suggested by [17].…”
Section: Discussionsupporting
confidence: 79%
“…The roles played by parents have significant impacts over the course of the lives of young people and allow them to engage and practice money management skills independently. In fact, evidence has shown that the roles played by parents are not restricted only to the field of personal finance behavior, but also applicable to other fields such as consumer socialisation, electricity consumption, education, psychology and eating behaviors (Aguirre-Bielschowsky, Lawson, Stephenson, & Todd, 2018;Jung, 2019). PFS is considered as a lifelong process where individuals are constantly exposed to new financial patterns, experiences, social roles and situations throughout their lives by their parents.…”
Section: Parental Financial Socialisation (Pfs)mentioning
confidence: 99%
“…nagging their children and children subsequently ignoring their parents, particularly when parents' own behavior was not consistent with their own instructions (Aguirre-Bielschowsky et al, 2018). Schmidt et al (2014) found the opposite, that parents perceived of their own children as significant energy consumers, due to a lifestyle more attuned to using smart phones and computers.…”
Section: Potential Energy Demand Conflict By Locationmentioning
confidence: 99%
“…In a study by Aguirre-Bielschowsky et al (2018) (which involved interviews with 26 children and a supervising parent, and three focus groups with a total of 14 children) children were found to have a higher perception of their level of control over energy using appliances than what their parent(s) thought they had, with children reporting that they in fact used more energy than what their parents allowed them. Furthermore, in the same study, reminders (i.e.…”
Section: Potential Energy Demand Conflict By Locationmentioning
confidence: 99%